Using Yogic Intervention Reduces Serum Lipids and Atherogenic Indices: A Comprehensive Study - Rahaman, Aminur; Pramanik, Tarak Nath (Physical Education Theory and Methodology, 2025)
Background. Optimal lipid regulation is a key determinant of cardiovascular health. Disturbances in lipid metabolism are associated with elevated cardiovascular risk. Yogic practices have demonstrated potential in modulating biochemical and cardiovascular parameters. Objectives. The present study aimed to investigate the effect of a twelve-week structured yogic practice intervention on selected lipid profile parameters, namely total cholesterol, triglycerides, high-density lipoprotein (HDL), low-density lipoprotein (LDL), very-low-density lipoprotein (VLDL), cholesterol/HDL ratio, triglyceride/HDL ratio, LDL/HDL ratio, and non-HDL/HDL ratio among male college students. Materials and Methods. Twenty-four students (aged 17–22 years) from Shyampahari Government Primary Teacher Training Institute, India, were randomly allocated into experimental (n = 12) and control (n = 12) groups. The intervention group practiced yoga for 1 hour/day, 6 days/week, over 12 weeks, while controls maintained routine activities. Venous blood samples were collected pre- and post-intervention and analyzed using an automated biochemical analyzer. Within-group differences were assessed using paired t-tests, and between-group comparisons employed independent t-tests. Statistical significance was set at α = 0.05. Results. The experimental group showed substantial reductions in total cholesterol (p = .041), triglycerides (p = .015), VLDL (p = .021), triglyceride/HDL ratio (p = .003), and non-HDL/HDL ratio (p = .003), alongside an increase in HDL (p = .045). Meanwhile, LDL (p = .524), LDL/HDL (p = .149), and cholesterol/HDL ratio (p = .469) remained unchanged. No significant changes were observed in the control group. Conclusions. The findings indicate that a structured yogic program improves lipid metabolism and cardiovascular efficiency, supporting yoga as an effective non-pharmacological intervention for young adults.